Analisis Faktor Penyebab Anak Tidak Melanjutkan Pendidikan Ke Jenjang Perguruan Tinggi Pada Keluarga Petani - Huba, Ratna Khatijah (Jurnal Pendidikan Sosiologi dan Humaniora, 2014)
This research aims to analyze the factors of family, neighbourhood, and society encourages children in Desa Mulia Kecamatan Teluk Keramat do not continue their study to the higher education. A descriptive study is employed in this research. Form of this research is case study involving farmer families whose children pass the senior high school but do not continue to higher education as the participants. The results reports that the factors which encourage them not to continue their study are; (1). family factor, indicated by economic stability, number of dependents in family, low of parent’s educational background, and lack of parent’s motivation and awaraness on education, (2). neighbourhood factor, represented by low of neighbourhood education and free sex, (3). society factor shown by low of education level of the society and lack of awareness on the importance of education.Keywords : Causative Factors, Higher Education, Farmer Family.